The Influence of Firm Size and Macroeconomic Factors on Financial Distress in IDX Public Listed Companies - Saragih, Hero Rexy; Widoretno, Astrini Aning (Universitas Medan Area, 2025)
Post-pandemic global economic uncertainty has heightened the risk of financial distress, particularly in the manufacturing sector, which is vulnerable to macroeconomic pressures. This study aims to analyze the influence of firm size, inflation, and exchange rate on financial distress in manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The research applies bankruptcy theory and signaling theory to explain the relationships between variables. A quantitative approach was employed using multiple linear regression on 510 observations from 170 companies. The findings reveal that firm size and exchange rate significantly affect financial resilience, while inflation has no significant impact. Large firms are more resistant to financial pressure, and rupiah depreciation benefits export-oriented companies. The novelty of this study lies in its focus on the post-pandemic period an underexplored timeframe and its integration of both internal and external factors in analyzing financial distress. These findings offer practical implications for corporate management in developing growth strategies and adaptive exchange rate risk management to enhance resilience against global economic shocks.